PENGARUH SUSTAINABILITY REPORT DAN GOOD CORPORATE GOVERNANCE TERHADAP PROFITABILITAS PERUSAHAAN MANUFAKTUR SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI 2021-2023 - Rahmadani, Khoiriah; Fauzi, Indra; Lubis, Reza Hanafi; Wardany, Sri (Worksheet : Jurnal Akuntansi, 2025)
This research aims to examine the effect of Sustainability reports and Good corporate governance on profitability in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. Determining the sample using the purposive sampling method, the sample was obtained by manufacturing companies in the 2021-2023 time period so that 30 observation data were obtained. The data used is secondary data and the data analysis technique used is multiple linear regression method by conducting a series of assumption tests to ensure the suitability of the data. The data processing used in this research uses panel data regression with the help of Eviews version 12 software. The results of this research show that sustainability reports have a positive and significant effect on profitability, good corporate governance has a positive and significant effect on profitability. Based on the results of the simultaneous test (F Test), it shows that all independent variables have an effect simultaneously or together on the dependent variable. Based on the predictive ability of these two variables, profitability is 75.68%, while the remaining 24.32% is influenced by other variables outside this research.